The Meanings of Signs in Oriflame Advertisement - Darmayasa, Komang Agus; Setianingsih, Ni Ketut Alit Ida; Adni, Nissa Puspitaning (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The study entitled "The Meanings of Signs in Oriflame Advertisement" is intended to analyze the verbal and visual aspects in the Oriflame Advertisement, to identity and analyze the verbal and visual signs in the advertisement, and to describe the function and the meaning of verbal and visual sign used in the advertisement. This study used library research, which applied the documentation method. The data data of this study were taken from the official websites of Oriflame in April 2019 and analyzed qualitatively with description techniques and the results of the research were presented in the form of description. This study applied the theory of signs which applied the Triadic of Sign proposed by Peirce cited in Butchler (2015), and the supporting theory of color by Cerrato (2012). The scope of this study was to discuss the verbal and visual signs that were used in the Oriflame Advertisement which include Skincare and a foundation product, and the function and meaning based on the theories that had been mentioned earlier. The result of this study showed that from the verbal aspect, the type of meaning contained in the advertisements was to inform information contained with fact and to persuade the readers to buy the products. Meanwhile, from the visual aspect, there were a lot of pictures, symbols, icons that could be found in the Oriflame advertisement. The meaning was also represented based on the Triadic of Signs. Besides, the colors that surrounded the advertisements played significant roles that were mostly dominated by white, green, and brown color.